An exploratory examination of order effects on CPA exam passage timeliness. (September 2016) - Bline, Dennis; Perreault, Stephen; Zheng, Xiaochuan
Highlights: We examine performance data on candidates taking the CPA exam. We test whether candidate performance differs based upon the order in which they sit for the exam sections. On average, certain orderings of the exam sections appear to be associated with more timely passage than others. Abstract: We examine whether the order in which candidates take individual sections of the CPA exam is related to their timeliness of passing all four parts. We examine performance data from 121, 234 unique candidates taking the exam during the period 2005–2013 and find that, on average, candidates who took the FAR section first passed all four sections more quickly than those who took any other section first. In addition, we find that candidates who took the BEC section first took, on average, significantly longer to pass the exam than those who took any other section first. We find some evidence that suggests that these findings are attributable to the fact that candidates who take and pass FAR (BEC) first were least (most) likely to lose credit for previously passed sections due to the requirement that all four sections of the examination be passed within an 18 month window. That is, candidates who take and pass FAR (BEC) first are least (most) likely to have to retake this section compared to all other sections.